Are young people safe on social media? Design of an instrument to measure media literacy competence in the view of social media risks - Barrezueta-Cabrera, Tania (2023)
Digital citizenship requires the population to be competent in surfing the web safely, healthily, and beneficially to avoid the constant dangers of their virtual environment. This article proposes a tool to assess the cognitive media literacy competence of young people aged 18 to 25 in the face of risks on social networks. It evaluates aspects such as knowledge of digital risks, the relationship of social networks with counter-values, and behaviors related to the consumption of risky content. The validation of the tool through the Delphi method and the application of a pilot test with over three hundred people demonstrate its effectiveness in assessing the media literacy aspects required for appropriate digital citizenship in the face of the current context’s dangers.